The effect of climatic factors on solar radiation and solar panels in Diyala Governorate (Journal of the College of Basic Education, 2023)
The climatic characteristics have a major role in the production of electric energy, and one of the most important things that can be relied upon in converting energy into renewable energy is solar radiation. The climatic elements, which in turn affect the amounts of solar radiation reaching the surface of the earth, the high values ​​of solar radiation in the summer can contribute to the production of electric energy, and thus we can reduce the pressure on the government electric energy, which increases the pressure on it in the summer, and the following is a breakdown of the most important Climatic characteristics in the study area.